PENERAPAN IT GOVERNANCE BERBASIS COBIT 4.1 PADA LEMBAGA PENDIDIKAN - Agatha Fatmawati Febriana; Weli Weli (SIMAK, 2020)
In line with the increasing use of information technology devices, organizationsneed to implement information technology strategies that are appropriate toorganizational goals. Likewise, the use of information technology for businessprocesses in the education industry needs to adopt information technologygovernance. This research aims to analyze the implementation of informationtechnology governance using the COBIT 4.1 framework. The subject of thisresearch is the Catholic University of Indonesia Atma Jaya Jakarta. Datacollection was carried out by survey method using a questionnaire aimed atinformation technology managers and several core users in several units.Descriptive analysis results found that the conditions of information technologygovernance and implementation at Atma Jaya Catholic University of Indonesiaare at level 3 using a scale of 0 to 5. This result means that the institution has aproper procedure and communicate the document. This research contributes toresearch related to the application of information technology governance,especially for educational institutions, as well as information technologymanagers as input in managing information technology resources in relatedinstitutions.information technology resources in related institutions.